Employee Empowerment and Innovative Work Behavior: The Moderating Role of Leader-Member Exchange - Kanake, Mercy Kananu; Kemboi, Ambrose (SEISENSE Journal of Management, 2020)
Purpose: This paper seeks to address the moderating effect of leader-member exchange on the link between employee empowerment and innovative work behavior. Design/Methodology: The study draws on the causal-comparative research design, and employs paper-based self-administered questionnaires to gather data from a sample of 470 employees drawn from manufacturing firms in Kenya. This sample is part of a population of 9915 employees and has been narrowed down using Yamane’s formula. The study employs stratified and simple random sampling techniques to constitute the required sample of employees. Findings: The results indicate that employee empowerment and Leader-Member Exchange positively and significantly affect innovative work behavior. The results further reveal that Leader-member exchange significantly moderates the link between employee empowerment and innovative work behavior. Practical Implication: The findings of this study provide an avenue through which managers of manufacturing firms can identify constructs that best explain innovative work behavior, especially during challenging times such as this time of Covid 19 pandemic. The results of this study provides managers with opportunities to come up with techniques, policies and strategies to improve relationship between employees and their supervisors for purposes of improved productivity, employee loyalty and reduced conflicts. Originality/Value: The study makes a novel attempt to show the moderating influence of leader–member exchange in the context of employee empowerment and innovative work behavior in manufacturing firms in Kenya. Moreover, the study underscores the importance of leader-member exchange in employees’ innovative behavior, which is vital knowledge in tough times like the current uncertainty caused by the covid-19 pandemic.